2017
DOI: 10.3389/fphar.2017.00429
|View full text |Cite
|
Sign up to set email alerts
|

UTP – Gated Signaling Pathways of 5-HT Release from BON Cells as a Model of Human Enterochromaffin Cells

Abstract: Background: Enterochromaffin cells (EC) synthesize and release 5-HT and ATP to trigger or modulate gut neural reflexes and transmit information about visceral/pain sensation. Alterations in 5-HT signaling mechanisms may contribute to the pathogenesis of IBD or IBS, but the pharmacologic or molecular mechanisms modulating Ca2+-dependent 5-HT release are not understood. Previous studies indicated that purinergic signaling via ATP and ADP is an important mechanism in modulation of 5-HT release. However, EC cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…Because EE and EC cells are electrically excitable ( 21 , 28 , 47 ), it is possible that Piezo2 generates a receptor potential that activates voltage-gated sodium channels, which mediate seconds-long EC cell-bursting activity ( 21 , 28 ), and activate voltage-gated calcium channels, which have been implicated in EC cell chemosensitivity ( 28 , 48 , 49 ). Another possibility is that Ca 2+ flux through Piezo2 directly activates EC cell Ca 2+ -induced Ca 2+ release ( 50 ) or ATP release and subsequent autocrine P2X activation ( 51 ). These possibilities are not mutually exclusive, and clarifying the involvement of these mechanisms in EC mechanotransduction may help delineate EC cell roles within the neuroepithelial ( 28 , 52 ) and endocrine ( 7 , 39 ) systems.…”
Section: Discussionmentioning
confidence: 99%
“…Because EE and EC cells are electrically excitable ( 21 , 28 , 47 ), it is possible that Piezo2 generates a receptor potential that activates voltage-gated sodium channels, which mediate seconds-long EC cell-bursting activity ( 21 , 28 ), and activate voltage-gated calcium channels, which have been implicated in EC cell chemosensitivity ( 28 , 48 , 49 ). Another possibility is that Ca 2+ flux through Piezo2 directly activates EC cell Ca 2+ -induced Ca 2+ release ( 50 ) or ATP release and subsequent autocrine P2X activation ( 51 ). These possibilities are not mutually exclusive, and clarifying the involvement of these mechanisms in EC mechanotransduction may help delineate EC cell roles within the neuroepithelial ( 28 , 52 ) and endocrine ( 7 , 39 ) systems.…”
Section: Discussionmentioning
confidence: 99%
“…EC cells represent around 50% of all EE cells that sense diverse dietary nutrients and metabolites to produce ~95% of total body 5-HT [ 14 ]. Studies conducted on human primary colonic EC cells and BON cells (immortalized cell line models of EC cells) found that 5-HT is released from EC cells in response to stimulation of luminal nutrients [ 11 , 14 , 15 , 85 ]. Unlike human primary colonic EC cells, BON cells release 5-HT following the stimulation of luminal D-glucose through sodium-glucose-linked transporter 1 (SGLT1) [ 86 ].…”
Section: 5-ht In the Gutmentioning
confidence: 99%
“…ATP and its breakdown products are a purinergic transmitter in the ENS, which can initiate enteric nerve reflex or activate afferent nerve endings to transmit pain to the brain. Through BON cells or EC cells isolated from human intestinal surgery specimens, it is verified that ECs can respond to ATP, uridine triphosphate (UTP) and uridine diphosphate (UDP), mainly by activating P2X3, P2Y4R and PLC/IP3/IP3R/SERCA Ca 2+ signaling pathways, to involve in visceral sensitization and pain production ( Xu et al., 2008 ; Liñán-Rico et al., 2017 ). In addition, metabolites of norepinephrine and isovalerate activate ECs to release 5-HT ( Bellono et al., 2017 ).…”
Section: Serotonin Signaling By Ecsmentioning
confidence: 99%